The antibacterial effect assay of a few officinal plants - Daniela Moţ; Ileana Nichita; Emil Tîrziu; Teodor Moţ (Scientific Papers Animal Science and Biotechnologies, 2023)
From very old times plants were used for man or animal health, with good results in slightly, functional injuries or in incipient stages of diseases. In chronic, when already appeared organic affection, officinal plants has an adjuvant part and can contributes to a partial reversibility of symptoms or lesions. This study was been performed using aqueous solutions or essential oils from Mentha spicata, Ocimum basilicum, Thymus vulgaris and Rosa sp. with  bacterial cultures on usual or special culture mediums of Bacillus cereus, Escherichia coli, Pseudomonas aeruginosa, Salmonella enterica and Staphylococcus aureus. In view of antibacterial assay emphasizing were been used small pieces of absorbent paper immersed in solutions or essential oils   above mentioned officinal plants. These pieces of papers then were been deposed in usual and special culture mediums containing the mentioned species of bacteria and then incubated 24 hours. The obtained result emphasized by the inhibition areas development recommend the antibacterial effect of essential oils of Rosa sp. (25.5 mm inhibition area), Mentha spicata (16.5 mm), Thymus vulgaris (7.3 mm) and Ocimum basilicum (5.1 mm) in therapeutic purpose, both in intern and extern way in infections caused by Bacillus cereus, Escherichia coli, Salmonella enterica and Staphylococcus aureus, in incipient stages.